The Effect of Dividends and Capital Gains on Underlying Assets in Green Sukuk - Agus Purnomo; Atika Zahra Maulida (Journal of Islamic Economics and Finance Studies, 2023)
Underlying assets are one of the required instruments for issuing sukuk to attract investors to invest in the Sharia capital market. Green sukuk is one of the sharia investment instruments issued by companies for retail sukuk products and has the aim of obtaining funding through debt securities or securities to encourage the company's growth and development performance through underlying assets. This research aims to determine the effect of dividends and capital gains on the underlying assets in retail sukuk. This research method uses a quantitative method with a descriptive approach. In collecting data, the random sampling method was used, where the research determined the number of samples using the Slovin method to know the number of samples and determine the sample categories for distributing questionnaires. The results of dividend research do have a significant influence on underlying assets. Based on the graph, dividend distribution has increased every year, thereby influencing the growth performance of underlying assets. A company will be said to be good if the income it earns is greater than its expenses, so it affects the company's assets. While capital gains also have a significant effect on the underlying assets in retail sukuk, it does not rule out the possibility that they will be influenced by other factors that are related to capital gains.   Underlying aset merupakan salah satu instrumen yang diperlukan dalam penerbitan sukuk untuk menarik minat investor berinvestasi di pasar modal syariah. Green sukuk merupakan salah satu instrumen investasi syariah yang diterbitkan perusahaan untuk produk sukuk ritel dan bertujuan untuk memperoleh pendanaan melalui surat utang atau surat berharga untuk mendorong pertumbuhan dan perkembangan kinerja perusahaan melalui aset yang mendasarinya. Penelitian ini bertujuan untuk mengetahui pengaruh dividen dan capital gain terhadap underlying asset pada sukuk ritel. Metode penelitian ini menggunakan metode kuantitatif dengan pendekatan deskriptif. Dalam pengumpulan data digunakan metode random sampling, dimana penelitian menentukan jumlah sampel dengan menggunakan metode Slovin untuk mengetahui jumlah sampel dan menentukan kategori sampel untuk penyebaran kuesioner. Hasil penelitian dividen memang mempunyai pengaruh yang signifikan terhadap aset dasar. Berdasarkan grafik, pembagian dividen mengalami peningkatan setiap tahunnya sehingga mempengaruhi kinerja pertumbuhan aset dasar. Suatu perusahaan akan dikatakan baik apabila pendapatan yang diperoleh lebih besar dibandingkan dengan pengeluarannya, sehingga mempengaruhi kekayaan perusahaan. Meskipun capital gain juga berpengaruh signifikan terhadap aset dasar sukuk ritel, namun tidak menutup kemungkinan hal tersebut akan dipengaruhi oleh faktor lain yang terkait dengan capital gain.